Groundwater Basin Openness and Sustainability - Chao Wang; Graham E. Fogg; Richard A. Pauloo (Water Resources Research)
Abstract Groundwater pumping from wells, together with water uses such as agricultural irrigation have been converting formerly open groundwater basins into closed systems that accumulate total dissolved solids (TDS). This process of anthropogenic basin closure and salinization (ABCSal) would appear to pose a threat to groundwater sustainability that is at least as formidable as groundwater overdraft and contamination from the surface, yet has been little explored. Models of groundwater flow and solute transport herein show that groundwater basin openness itself should be considered a primary determinant of sustainability. Results show that groundwater basin closure is a threshold condition that sets the aquifer system on a path of increasing salinity that can only be halted by opening the basin. Further, the magnitude of groundwater pumping and degree of basin closure significantly influence the spatial distribution of salinity. In open basins, salinity approaches dynamic equilibrium over long‐term conditions. Stratification of higher‐TDS groundwater overlying lower‐TDS groundwater occurs below farmlands whose irrigation‐supplying wells are impacted by irrigation return flow from upstream farmlands, and act to redistribute relatively saline groundwater to the land surface. More intensive pumping leads to groundwater basin closure and more vertically‐oriented groundwater flow toward pumping wells. TDS retainment in the basin and repeated well capture, re‐distribution as irrigation water, and evapoconcentration lead to progressive salinization. Regardless of basin closure status, fresh recharge protects nearby downstream portions of the basin from salinization, indicating that managing or limiting the spread of contaminated groundwater may be achieved via managed aquifer recharge of good quality water.